A inserção da plataforma GeoGebra na fase do estágio de regência de um curso de licenciatura em matemática no Tocantins - Oliveira, Elizeu Martins (Universidade Federal do Tocantins, 2023)
This study aimed to present the necessary knowledge for an intern of the Degree in Mathematics to teach mathematics in the regency phase, as well as to investigate in published works the contributions of LEM to the intern, to know how Virtual Learning Environments work, and from this knowledge, direct how the intern can use the GeoGebra virtual platform to think and plan their actions in the classroom. It also sought to present the role of the teacher and the student within a mathematics teaching laboratory. For the development of this study, the exploratory research method was used mainly to build the Mathematics Teaching Laboratory (LEM) on the GeoGebra virtual platform, which was designed from the challenges faced by the interns of the degree course, at the time they developed the planning from their activities to work in the classroom, without having the knowledge of the GeoGebra platform to help at that moment. Finally, through this study it was possible to show how this platform is of great help for the planning of classes and activities.